Benzyl Benzoate Isolation from Acridocarpus smeathmannii (DC.) Guill. & Perr Roots and Its Bioactivity on Human Prostate Smooth Muscle Contractions - Oluwafemi Ezekiel Kale; Iskander Rauanov; Claudia Huber; Alexander Tamalunas; Christian G. Stief; Wolfgang Eisenreich; Martin Hennenberg (Pharmaceuticals)
Background/Objectives: This study is the first report on isolating a natural benzyl benzoate (nBB) from Acridocarpus smeathmannii (DC.) Guill. & Perr roots. Methods: The structure was verified using GC-MS, HPLC-UV-VIS, and two-dimensional NMR. Since it is known for its vasodilatory and anti-spasmolytic actions, we investigated the biological effects of nBB on human prostate smooth tissue (rPx) obtained from a radical prostatectomy. For this purpose, rPx was incubated with nBB (0.05, 0.25, or 0.5 µM) in an organ bath, and then cumulative concentration–response curves were constructed for adrenergic agonists and electrical field stimulation (EFS). Results: Adding the various concentrations, nBB showed potential inhibition during agonist-induced contractions (0.1–100 µM). Also, neurogenic contractions of rPx by EFS (2–32 Hz) were reduced by up to 57%. Conclusions: Overall, this study reports on an efficient protocol of nBB isolation from A. smeathmannii and its contractility effects on human prostate smooth muscle. Potentially, this could contribute to the natural production of BB from A. smeathmannii species while giving it evolutionary recognition. However, since BB influences prostate smooth muscle contractility, caution in patients taking herbal supplements containing nBB is essential, as this may play a role in contributing to the symptoms of urinary tract conditions.